Penganggaran Untuk Pengendalian Organisasi Di BUMDes Rukun Makmur - Sukma Mardaning Poncowati; Noni Christia Firdianti; Aditya Pradina Hermawan; Niken Wahyuningtyas; Faneshia Tangke Rerung; Hafid Pramaisvara; Agnes Deta Ardina (Universitas Kristen Satya Wacana Salatiga, 2020)
Organizational control is needed by both business and non-business organizations, business organizations have the main goal of getting profit and for non-businesses it has a goal for public services. Village-Owned Enterprise (BUMDes)